MicroRNAs in inflammatory bowel disease: What do we know and what can we expect? - de Oliveira, Ellen Cristina Souza [UNESP]; Quaglio, Ana Elisa Valencise; Grillo, Thais Gagno [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Baishideng Publishing Group, 2024)
MicroRNAs (miRNAs), small non-coding RNAs composed of 18–24 nucleotides, are potent regulators of gene expression, contributing to the regulation of more than 30% of protein-coding genes. Considering that miRNAs are regulators of inflammatory pathways and the differentiation of intestinal epithelial cells, there is an interest in exploring their importance in inflammatory bowel disease (IBD). IBD is a chronic and multifactorial disease of the gastrointestinal tract; the main forms are Crohn's disease and ulcerative colitis. Several studies have investigated the dysregulated expression of miRNAs in IBD, demonstrating their important roles as regulators and potential biomarkers of this disease. This editorial presents what is known and what is expected regarding miRNAs in IBD. Although the important regulatory roles of miRNAs in IBD are clearly established, biomarkers for IBD that can be applied in clinical practice are lacking, emphasizing the importance of further studies. Discoveries regarding the influence of miRNAs on the inflammatory process and the exploration of their role in gene regulation are expected to provide a basis for the use of miRNAs not only as potent biomarkers in IBD but also as therapeutic targets for the control of inflammatory processes in personalized medicine.
Keywords: Biomarker; Crohn’s disease; Inflammatory bowel disease; MicroRNAs; Therapy; Ulcerative colitis